Kebutuhan Kapasitas Fasilitas Land Side Untuk Tahun 2015 Sebagai Upaya Meningkatkan Kenyamanan Penumpang Di Bandar Udara Pattimura Ambon - Lukiana Lukiana (Research and Development Agency of The Ministry of Transportation, 2012)
In accordance to the Acceleration and Extension of Indonesian Economy Development (MP3EI) in Maluku from 2011 to 2025, PT (Persero) Angkasa Pura I is going to extend the terminals and aprons in Pattimura Airport, Ambon. The extension of passenger terminals is necessairily important because terminal area in an international airport has to be wide enough to improve passengers’ convenience along with the increasing passengers’ movement every year. In relation, in order to figure out the minimum land side capaicty needs of Pattimura Airport Ambon in 2015 that complies to the passengers’ movement development prediction in the same year, it is necessary to conduct a study on the landside facility needs as an effort to improve passengers’ convenience.From the sum result of passengers’ number at peak hour as predicted in 2015 which is 848 passengers, the minimum size of the departure hall area is 1993 m2, check in area is 297 m2, boarding room is 1329 m2 and baggage claim area is 845 m2. Berdasarkan Masterplan Percepatan dan Perluasan Pembangunan Ekonomi Indonesia (MP3EI) di Maluku Tahun 2011-2025, PT. (Persero) Angkasa Pura I akan melakukan pengembangan terminal dan apron Bandar Udara Pattimura Ambon. Perluasan terminal penumpang sangat diperlukan karena sebagai bandar udara internasional, luas terminal akan meningkatkan kenyamanan penumpang mengimbangi meningkatnya jumlah pergerakan penumpang pertahun.terkait dengan hal tersebut di atas, untuk mengetahui kebutuhan kapasitas landside minimal Bandar Udara Pattimura Ambon pada tahun 2015 sesuai dengan perkiraan perkembangan pergerakan penumpang pada tahun tersebut, maka perlu dilakukan pengkajian terkait dengan kebutuhan fasilitas landside sebagai upaya meningkatkan kenyamanan penumpang.Dari hasil perhitungan dengan jumlah penumpang pada waktu sibuk yang diperkirakan pada tahun 2015 sebanyak 848 penumpang maka luas hall keberangkatan minimal 1993 m2 , check in area minimal 297m2 , luas ruang tunggu keberangkatan minimal 1329 m2 , luas baggage claim area minimal 845m2 , dan luas ruang tunggu keberangkatan minimal 1329 m2.